A view to a kilt: the late Bronze age aegean costume in the context of social and cultural changes : Abhandlung - Franković, Filip (Prähistorische Zeitschrift, 2023)
The connection between the Late Bronze Age (LBA) Aegean costumes and social, cultural and political changes is a rather unexplored topic. Probably the only exception are kilts, the connection of which to such changes on Crete during the 15 th century BCE remains a commonly discussed topic in studies focusing on the LBA Aegean iconography and other data sets. However, many questions remain open and the topic is far from exhausted. In this paper I build on the work of various scholars who have studied LBA Aegean kilts in the context of social, political and cultural changes. I diachronically study the changes in the representations of kilts since the beginning of the LBA in the Aegean until the end of the Palatial period on the Greek Mainland (ca. 1700/1600-1200 BCE). Moreover, I examine the spatial distribution of specific kilt types in different periods. In cases of several different kilt types appearing in contemporary contexts in the same region, I explore whether similar costumes might have had different social connotations within the same communities. Moreover, I examine the influence of elite power structures and socio-political changes on the perception of kilts. However, I do not observe kilts as passive reflections of specific social, cultural and political contexts, but rather as material forms actively used in the creation of social realities.